Feasibility of an Interdisciplinary Intervention to Promote Balance Confidence in Lower-Limb Prosthesis Users: A Case Study. Issue 2 (9th April 2023) - Churchill, Rachel; Schneider, Kristin L.; Calamari, John E.; Henderson, Roberta; Hwang, Sungsoon; Major, Matthew J.; Duncan, Chad; Stachowiak, Aaron; Reddin, Christopher; Rosenblatt, Noah J.
ABSTRACT: Introduction: Low confidence in ones' ability to maintain balance during daily activities is a prevalent issue for lower-limb prosthesis users (LLPUs) that negatively impacts psychosocial function but is not currently addressed in rehabilitation. The purpose of this case study was to demonstrate feasibility of an intervention that combines cognitive behavioral therapy techniques with physical therapy to increase balance confidence, reduce avoidance behaviors, and increase community participation in LLPU. Materials and Methods: A 58-year-old man with a unilateral transtibial amputation completed eight 120-minute intervention session, which included physical therapy in the form of virtual reality active gaming targeting balance and gait adaptability, followed by psychoeducation, cognitive restructuring, and a brief exposure exercise. The intervention was intended to improve balance and gait while addressing beliefs regarding physical abilities and their impact on behavior. All exercises were individually tailored to address real-world, subject-specific distress-inducing situations, identified jointly by a licensed physical therapist and behavioral counselor that were present throughout all intervention sessions. The primary outcome, balance confidence, was quantified before, during, immediately after, and 1 month after completion of the intervention. Additional measures of physical function and community participation were also assessed. Results: Objective balance measures (Berg Balance Scale) improved by 9 points from baseline to follow-up, and balance confidence improved from 48.5% at baseline to 91.9% at 1-month follow-up. Gains in gait self-efficacy and reductions in fear-avoidance behavior mirrored this change. Conclusions: This case study demonstrates that a multicomponent intervention is feasible and may provide a positive and helpful experience for LLPU to meaningfully improve balance confidence and reduce avoidance behavior.